Sequential injection system for the enzymatic determination of ethanol in alcoholic beverages with in-line dilution - Pais, Teresa F. M. (2013)
A sequential injection system for the enzymatic determination of ethanol in wines with spectrophotometric detection was developed. The determination was based on the enzymatic reaction involving ethanol and NAD(+) in the presence of alcohol dehydrogenase. A gas-diffusion unit was introduced in the system to perform an in-line dilution. It was possible to operate the system with a reagent consumption of 1.3 mg of NAD(+), 0.45 U of ADH, and 32 mu L of sample, per assay with a determination rate of 21 h(-1). The results obtained from the analysis of wine samples were statistically equivalent to those obtained by the reference method, with good repeatability; the relative standard deviation (n = 10) was <1% with a LOQ of 0.3% (v/v). (C) 2012 Elsevier Ltd. All rights reserved.